2011
DOI: 10.3177/jnsv.57.426
|View full text |Cite
|
Sign up to set email alerts
|

β-Cryptoxanthin Suppresses the Adipogenesis of 3T3-L1 Cells via RAR Activation

Abstract: SummaryWe recently reported that the oral intake of ␤ -cryptoxanthin exerted anti-obesity effects by lowering visceral fat levels. In the present study, we characterized the molecular mechanisms underlying the lipid-lowering effects of ␤ -cryptoxanthin on 3T3-L1 cells. Consistent with our previous findings, ␤ -cryptoxanthin rapidly reduced the level of intracellular lipids in 3T3-L1 cells as assessed by Oil red O staining. Using an in vitro nuclear receptor binding assay, we demonstrated the ability of ␤ -cryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 24 publications
4
28
1
Order By: Relevance
“…Combined with their results on fucoxanthin and fucoxanthinol, they suggested that carotenoids containing an allene bond and an additional hydroxyl substituent on the side group may show suppressive effects on adipocyte differentiation in 3T3L1 cells. [102][103][104]117 It should be noted that their observation is not in agreement with the results obtained by Shirakura et al using β-cryptoxanthin 101 or García-Rojas et al using lutein in a bovine adipocyte-differentiation system, in which 30 µM lutein increased PPARγ mRNA expression. 62 Perhaps the hydroxyl group at the third position of the ionone ring is also important for carotenoid effects.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…Combined with their results on fucoxanthin and fucoxanthinol, they suggested that carotenoids containing an allene bond and an additional hydroxyl substituent on the side group may show suppressive effects on adipocyte differentiation in 3T3L1 cells. [102][103][104]117 It should be noted that their observation is not in agreement with the results obtained by Shirakura et al using β-cryptoxanthin 101 or García-Rojas et al using lutein in a bovine adipocyte-differentiation system, in which 30 µM lutein increased PPARγ mRNA expression. 62 Perhaps the hydroxyl group at the third position of the ionone ring is also important for carotenoid effects.…”
contrasting
confidence: 54%
“…Their results indicated that β-cryptoxanthin inhibited 3T3L1 adipogenesis via the downregulation of PPARγ through RAR activation. 101 Fucoxanthin is a major carotenoid present in edible seaweed, such as Undaria pinnatifida and Hizikia fusiformis. Fucoxanthin and its metabolites, fucoxanthinol and amarouciaxanthin A, inhibited the adipocyte differentiation of 3T3L1 cells through downregulation of PPARγ and C/EBPα.…”
Section: Other Carotenoidsmentioning
confidence: 99%
“…In the present study, we found that not only intracellular lipid-droplet formation but also the gene expression and production of PLIN1 was suppressed by β-CRX in differentiated hamster sebocytes. A similar inhibition of lipid-droplet formation has been reported to be observed in β-CRX-treated mouse 3T3-L1 adipocytes [31]. Therefore, the β-CRX-inhibition of lipid-droplet formation is likely to include the transcriptional suppression of PLIN1 production in hamster sebocytes.…”
Section: Discussionmentioning
confidence: 49%
“…In addition, β-CRX is a vitamin A precursor, which is oxidatively cleaved to vitamin A by β-carotene 15,15'-dioxygenase [29], and can be stably stored in some tissue for several months [30]. Taken together with a recent report by Shirakura et al [31] where β-CRX inhibits the intracellular lipid-droplet formation in mouse 3T3-L1 adipocytes, we hypothesize that, instead of retinoids such as atRA and 13-cisRA, β-CRX is an effective candidate for acne therapy by modulating sebaceous lipogenesis. However, it is not fully understood whether β-CRX directly suppresses sebum production and accumulation in sebaceous gland cells (sebocytes) or not.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation